PERANCANGAN APLIKASI KIDSAFE EDUKASI PENCEGAHAN PELECEHAN DAN KEKERASAN SEKSUAL PADA ANAK USIA SEKOLAH DASAR BERBASIS ANDROID - Selvi afmailia; Gina Silvia; Ray Fadly Hadi; Farah Rakhimy Az Zahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
KPAI reported over 2,000 cases in 2022, many of which involved primary school-aged children. This study aims to develop the KidSafe educational app as an innovative solution for the prevention of sexual abuse and violence. The research method employed was qualitative descriptive, with data collection comprising observation, interviews, and literature review. Meanwhile, software development utilised the waterfall model. The research findings indicate that the KidSafe application is effective in enhancing children’s understanding of how to protect themselves from sexual abuse and violence.